Economic-mathematical and ecological-power aspects of dry mass usage as alternative source of energy - Matsiuk, D. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers economic-mathematical and ecological-power aspects of dry mass usage as alternative source of energy in Ukraine, in particular in Vinnitsa region on the example of straw . The conclusion is proved that burning of dry biomass in modern highly effective boilers will solve the problem heat-supply of settlements of Podolsk region.